Design, Synthesis, and Application of Carbon Dots With Synergistic Antibacterial Activity - Qie, Xingwang; Zan, Minghui; Gui, Ping; Chen, Hongyi; Wang, Jingkai; Lin, Kaicheng; Mei, Qian; Ge, Mingfeng; Zhang, Zhiqiang; Tang, Yuguo; Dong, Wen-Fei; Song, Yizhi (Frontiers in Bioengineering and Biotechnology, 2022)
The diversity of bacteria and their ability to acquire drug resistance lead to many challenges in traditional antibacterial methods. Photothermal therapies that convert light energy into localized physical heat to kill target microorganisms do not induce resistance and provide an alternative for antibacterial treatment. However, many photothermal materials cannot specifically target bacteria, which can lead to thermal damage to normal tissues, thus seriously affecting their biological applications. Here, we designed and synthesized bacteria-affinitive photothermal carbon dots (BAPTCDs) targeting MurD ligase that catalyzes the synthesis of peptidoglycan (PG) in bacteria. BAPTCDs presented specific recognition ability and excellent photothermal properties. BAPTCDs can bind to bacteria very tightly due to their chiral structure and inhibit enzyme activity by competing with D-glutamic acid to bind to MurD ligases, thus inhibiting the synthesis of bacterial walls. It also improves the accuracy of bacteria treatment by laser irradiation. Through the synergy of biochemical and physical effects, the material offers outstanding antibacterial effects and potentially contributes to tackling the spread of antibiotic resistance and facilitation of antibiotic stewardship.